Implementasi Program pada Satuan Pendidikan Non Formal Kota Padang Panjang - Suci Alfioni; Febri Yuliani (Jurnal Humaniora dan Ilmu Pendidikan, 2022)
Purpose: Based on the background and a number of problem formulations above, the goal that the researcher wants to achieve is to know the implementation of the Non-Formal Education Program in the Padang Panjang City Non-Formal Education Unit and to know the challenges of implementation. Research methodology: This type of research uses a descriptive study with a qualitative approach. Results: This program has been running well, this is evidenced by the many changes that occurred after the learning activity studio was made an Education Unit, such as changes in terms of better facilities and infrastructure and changes in terms of better education, only in terms of human resources which are still not optimal. Limitations: This study examines the Implementation of Non-Formal Education Programs in Non-Formal Education Units in Padang Panjang City, in this case the researcher uses the theory of Policy Implementation which consists of several components proposed by George C. Edward III in 2010. Contribution: The existence of this research is able to be useful as input and improvement material for the authorities and related parties in this case to deal with the poor in Indonesia, enriching the reference literature in the Faculty of Social and Political Sciences, especially the Public Administration Science Study Program, and being able to act as a reference for researchers. future who want to raise a similar discussion.